Impact of despotic leadership and workplace incivility on innovative work behavior of employees: Application of mediation-moderation model - Shahid Mehmood; Riffut Jabeen; Muhammad Asif Khan; Mohammed Arshad Khan; Beata Gavurova; Judit Oláh (Heliyon, 2023)
Innovative Work Behavior (IWB) of employees is one of the essential requirements for organizations to excel in competition in today's dynamic world. Nowadays, organizations can keep the current pace through competitive advantage. But to acquire competitive advantage, employees must be creative and innovative in their work-related behaviors. Small and Medium Enterprises (SMEs) in Pakistan are suffering several challenges in this regard. Therefore, current study is designed to examine the role of negative events and negative leadership on the IWB of the employees with mediating role of Psychological Well-being (PsyWB). Further, the moderating role of Perceived Organizational Support (POS) has also been tested. The negative event used in current research is Workplace Incivility (WPI) and Despotic Leadership (DL) from the negative leadership styles examined. Results of the current study showed that the presence of WPI and DL in organizations damage the IWB of employees as they harm the PsyWB of employees. We find that PsyWB mediated the relationship among DL, WPI, and IWB. POS is helpful for employees to overcome the negative issues prevailing in the organizations. The SMEs need to construct policies to eradicate WPI and must discourage despotic personalities to make the environment favorable for employees to protect their IWB. There must be some events that can increase the positive PsyWB of employees to make them more creative and motivated. Likewise, POS must be at sufficient level so that employees feel safe and healthy in all respects.